Investigating the searching behavior of Sino-U.S. relations in China based on complex network - Chen, Jun; Wang, Lei; Weng, Wuyan (Frontiers in Physics, 2023)
The Sino - U.S. relationship is one of the most important bilateral relationships in the literature of global geopolitics. Not only the two countries, but also other nations in the relevant regions have been influenced by their economic, cultural, political, educational, and diplomatic relations. Since Donald Trump administration's new nationalism, the "America First" policy was announced, globalization has been increasingly challenged by regional protectionism. When the Biden administration came to power, its foreign policy line was slightly different from its predecessor. However, the main topic of suppressing China's all-round development has never changed. The increasingly fierce competition between the two countries has attracted the attention of scholars in the fields of international relations and geopolitics. In order to analyze the Sino-U.S. relationship from the aspect of visibility graph, this paper conducted the time series data from Baidu searching index of the keyword “Sino-U.S. relations” from 2011 to 2021 into a directionless and authoritarian network, and studied its dynamic characteristics. The results provide a new perspective for analyzing the time series characteristics of Sino-U.S. relations. We can draw the conclusion that when the news made Sino – U.S. a trending topic on the internet, it would usually attract attention of many Chinese netizens to follow up the following stories, the searching index will also increase dramatically in a short period of time. Besides, from the time series data, it has been found that the relationship between the data is closer with more edges, greater degrees, and larger clustering coefficients. Meanwhile, the shorter the average path length, the shorter the path from data to another, the closer the relationship between the data.